The UN Goldstone Report and Retraction: An Empirical Investigation - Arye L. Hillman; Niklas Potrafke (Center for Economic Studies and ifo Institute (CESifo), 2015)
The United Nations Goldstone Report criminalized self-defense against state-sponsored or state-perpetrated terror. We use voting on the two UN General Assembly resolutions relating to the Goldstone Report to study whether support for the Goldstone principle of criminalization of self-defense against terror was influenced by countries' political institutions. Our results, using two different measures of political institutions, reveal systematic differences in voting by democracies and autocracies: as an example, based on the Chief-in-Executive measure of political institutions, a country with the highest democracy score was some 55 percentage points less likely to vote in favor of the second of the two UN Goldstone resolutions and some 55 percentage points more likely to abstain than a country with the highest autocratic score. The differences between democracies and autocracies in willingness to initiate symmetric welfare are therefore also reflected in differences in sensitivities to loss of life and harm in asymmetric warfare, through broad support by democracies, but not by autocracies, for legitimacy of self-defense against state-supported or state-perpetrated terror. The Goldstone Report is unique among United Nations reports in having been eventually repudiated by its principal author.
Keywords: 330; state-sponsored terror; state-perpetrated terror; asymmetric warfare; United Nations; UNGA voting; international law; war crimes; human rights; democracy; autocracy; Israel; supreme values; expressive voting